2010
DOI: 10.1038/sj.bjc.6605491
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cells demonstrate an altered response to hypoxia and an aggressive phenotype

Abstract: BACKGROUND: Tumours contain hypoxic regions that select for an aggressive cell phenotype; tumour hypoxia induces metastasisassociated genes. Treatment refractory patients with metastatic cancer show increased numbers of circulating tumour cells (CTCs), which are also associated with disease progression. The aim of this study was to examine the as yet unknown relationship between hypoxia and CTCs. METHODS: We generated human MDA-MB-231 orthotopic xenografts and, using a new technology, isolated viable human CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 37 publications
5
87
0
Order By: Relevance
“…In addition to this syngeneic mouse model, we selected the MDA-MB-231 human breast tumor cell line, as previous studies have shown this model to be hypoxic and to have hypoxia-inducible levels of CAIX (40,41). We confirmed the effect of hypoxia on CAIX expression in these cell lines to validate them as appropriate models for subsequent in vivo studies.…”
Section: Preclinical Models For Interrogating the Requirement Of Hypomentioning
confidence: 64%
“…In addition to this syngeneic mouse model, we selected the MDA-MB-231 human breast tumor cell line, as previous studies have shown this model to be hypoxic and to have hypoxia-inducible levels of CAIX (40,41). We confirmed the effect of hypoxia on CAIX expression in these cell lines to validate them as appropriate models for subsequent in vivo studies.…”
Section: Preclinical Models For Interrogating the Requirement Of Hypomentioning
confidence: 64%
“…When cancer spreads from the primary tumor to distant sites, cells enter into the bloodstream and exist in suspension until they reach a metastatic site. Patrikainen et al (33) and Ameri et al (34) observed that PC-3 prostate cancer cells and human MDA-MB-231 breast cancer cells which have a strong potential for distant metastasis and an increased capacity for colony formation exhibit an elevated expression of ASNS. Its increased abundance in metastasizing cells suggests that ASNS activity is beneficial for cancer cell survival once they detach from the primary tumor and enter the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished homologous recombination may lead to genetic instability by shifting the balance between the high-fidelity homologous recombination and the error-prone NHEJ pathways of double-strand break repair in primary tumor cells [83]. It was recently demonstrated that CTC that were released from the primary tumor show an altered phenotype compared to the parental tumor cells [85]. These CTC show a hypoxic phenotype with overexpression of HIF-1 alpha, asparagine synthetase and GLUT1.…”
Section: The Wall: Structure Of Blood Vessels In Tumor Cell Disseminamentioning
confidence: 99%
“…Cancer cell survival in the bone marrow environment was supported by Src facilitating CXCL12-CXCR4-AKT signalling and conferring resistance to TRAIL [45]. Second, cell lines-especially MDA-MB-231 cells in breast cancer-with their own specific differentiation status and metastatic potential [97] were frequently used as cellular models, e.g., for cellular adaptation strategies and site specific dissemination [60,85,98,99]. These experiments additionally show that differentiated cells are one source to produce tumors.…”
Section: Intrinsic Factors Affecting the Evolvement Of Novels Tumor Cmentioning
confidence: 99%